CTLA-4 Facilitates DNA Damage–Induced Apoptosis by Interacting With PP2A - Yan, Qiongyu; Zhang, Bin; Ling, Xi; Zhu, Bin; Mei, Shenghui; Yang, Hua; Zhang, Dongjie; Huo, Jiping; Zhao, Zhigang (Frontiers in Cell and Developmental Biology, 2022)
T lymphocytes are constantly exposed to endogenous and extracellular stress that likely lead to many types of damage to DNA. Maintaining genome stability is critical for faithful genome inheritance and prevention of mutagenesis. CTLA-4 is an inhibitory molecule found on T cells. They accumulate in the intracellular compartment, travel to the cell surface and rapidly internalize. However, the cytoplasmic function of CTLA-4 remains largely unknown. Here, we found that upon DNA damage, cytoplasmic of CTLA4 activated ATM by sequestering the ATM inhibitor PP2A into cytoplasm, further activating downstream targets, arresting cell cycle at the G2/M phase, and inducing cell apoptosis. This report showed the importance of CTLA-4 for the maintaining the stability of the genome and its molecular mechanisms.